2020
DOI: 10.1088/1612-202x/abd172
|View full text |Cite
|
Sign up to set email alerts
|

Goos–Hänchen shift of a mid-infrared femtosecond filament visualized by the laser coloration method

Abstract: We present the results of investigation of total internal reflection of a femtosecond light filament in a LiF crystal in the regime of anomalous group velocity dispersion. We measure the Goos–Hänchen shift of the filament in the vicinity of the critical angle for a single femtosecond pulse using the laser coloration method. The obtained experimental values are compared to several existing theoretical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…In this paper, by using the first order Taylor expansion of the Fresnel coefficients, we find an analytic expression for the intensity of the optical beam reflected by and (upper) transmitted through a dielectric prism, see Eq. ( 8) and (22). The closed expressions are then verified by numerical calculations for incidence near the Brewster angle showing an excellent agreement as can be seen in Figure 2.…”
Section: Conclusion V Conclusionsupporting
confidence: 62%
See 4 more Smart Citations
“…In this paper, by using the first order Taylor expansion of the Fresnel coefficients, we find an analytic expression for the intensity of the optical beam reflected by and (upper) transmitted through a dielectric prism, see Eq. ( 8) and (22). The closed expressions are then verified by numerical calculations for incidence near the Brewster angle showing an excellent agreement as can be seen in Figure 2.…”
Section: Conclusion V Conclusionsupporting
confidence: 62%
“…This study also showed the lateral displacement dependence on the angular distribution shape of the incoming beam. The theoretical prediction were confirmed by the experiments described in [21,22].…”
Section: Introduction I Introductionsupporting
confidence: 66%
See 3 more Smart Citations